2022
DOI: 10.3389/fonc.2022.934110
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Tumor Size, Volume and Tumor Volume Reduction Rate During Concurrent Chemoradiotherapy in Patients With Cervical Cancer

Abstract: ObjectiveThis study aimed to investigate the relationship between prognostic and tumor parameters of cervical cancer patients, such as tumor size (TS), tumor volume (TV), and tumor volume reduction rate (TVRR) after external beam radiotherapy.MethodsA total of 217 patients with advanced cervical cancer, classified as Federation of Gynecology and Obstetrics (FIGO) IIa–IVa, were enrolled in the study. Pre- and mid-RT pelvic magnetic resonance imaging (MRI) were performed twice, during RT and just before brachyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
4
1
Order By: Relevance
“…Therefore, we conducted a subgroup analysis of patients with and without concurrent chemotherapy and found that in patients receiving CCRT, TVR had important prognostic value in both OS and PFS. This is consistent with a number of previous studies [9,10,15]. It is worth noting, however, that among patients who received RT alone, TVR was not signi cantly associated with OS.…”
Section: Analysis Of Different Risk Subgroups Of Lacc Patientssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, we conducted a subgroup analysis of patients with and without concurrent chemotherapy and found that in patients receiving CCRT, TVR had important prognostic value in both OS and PFS. This is consistent with a number of previous studies [9,10,15]. It is worth noting, however, that among patients who received RT alone, TVR was not signi cantly associated with OS.…”
Section: Analysis Of Different Risk Subgroups Of Lacc Patientssupporting
confidence: 92%
“…Although previous studies have shown that TVR is signi cantly associated with prognosis in CC patients, the cut-off values used by different studies vary widely [8-10] and most of the previous studies have set the median as the continuous tumor reference cut-off. Therefore, Sun et al [15] used a more scienti c 'Youden index' as the cut-off value and found that among 217 LACC patients who received CCRT, patients with TVR ≥ 82.19% had a better prognosis. We also used the Youden index to determine the optimal cutoff value for patients and found that this was different from the results of previous studies.…”
Section: Analysis Of Different Risk Subgroups Of Lacc Patientsmentioning
confidence: 99%
“…The size of the initial tumor represents another factor with a major impact on survival. In general, between mortality and the size of the tumor is a directly proportional relationship, but if a favorable response to neoadjuvant therapy is obtained, the survival rate increases [20,21]. In our study, however, this parameter did not appear to be statistically significant, but these results may be influenced by the small number of patients.…”
Section: Discussioncontrasting
confidence: 82%
“…Several studies have shown that tumor reduction determined on MRI during EBRT was a significant prognostic factor ( 6 , 7 , 16 , 17 ). Most of these studies used treatment without CS and reported a cutoff value of 80–90% tumor volume reduction during EBRT of 45–50 Gy.…”
Section: Discussionmentioning
confidence: 99%